(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The rapid progression and widespread integration of Information and Communication Technology have ushered in a new era of sweeping social and legal transformations. Among the many groundbreaking advancements, Artificial Intelligence (AI) has emerged as a pivotal force, permeating nearly every facet of our daily lives. From commerce and industry to healthcare, transportation, and entertainment, AI technologies have become indispensable tools shaping how we interact, work, and navigate the world. While AI holds great potential, it could threaten democracy and its principles if misused. Indeed, the Italian Constitution protects humans’ fundamental rights of freedom (physical freedom, freedom of speech, association, reunion, etc.) as the main base to develop the democratic discourse and dialogue. AI, in this scenario, can potentially bypass this fundamental protection, representing a major threat to representative democracy. This article first describes the concepts of AI and discusses its benefits for society. It then focuses on the principles of representative democracy as they appear in the Italian Constitution and highlights potential algorithmic threats towards representative democracy itself. Finally, the paper offers possible solutions to counter algorithmic threats to democracy.